Capital mobility, tax competition, and lobbying for redistributive capital taxation - Jens Oliver Lorz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper analyzes the impact of international capital mobility on redistributive capital taxation and on lobbying activities by interest groups. It employs a model where different capital endowments lead to a conflict between households concerning their most preferred capital tax rate. Three main results are derived: First, redistributive source based capital taxes or subsidies decline as international tax competition intensifies. Second, lobbying activities of certain interest groups may explain international differences in the capital tax rate. Third, capital mobility may lead to declining lobbying activities of interest groups and thus may be welfare increasing for all households.
Keywords: F42; H77; 330; Tax competition; interest groups; redistribution